Learning the clinical method in the current medical training. A polemic, needed and urgent reflection - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The Clinical Method is a core issue in medical training. In this article a reflexive analysis is developed, conducted by a series of questions which involve the participants in the teaching learning process and the elements of the institutional policy. The questions are about the factors which could be seriously affecting the quality of learning the clinical method in the present conditions of the undergraduate medical teaching practice. The situation requires a critical view to be solved.